Psychological Outcomes of Living Liver Donors From a Multicenter Prospective Study: Results From the Adult‐to‐Adult Living Donor Liver Transplantation Cohort Study2 (A2ALL‐2). Issue 5 (3rd January 2017) - Butt, Z.; Dew, M. A.; Liu, Q.; Simpson, M. A.; Smith, A. R.; Zee, J.; Gillespie, B. W.; Abbey, S. E.; Ladner, D. P.; Weinrieb, R.; Fisher, R. A.; Hafliger, S.; et al.
Abstract : Although single‐center and cross‐sectional studies have suggested a modest impact of liver donation on donor psychological well‐being, few studies have assessed these outcomes prospectively among a large cohort. We conducted one of the largest, prospective, multicenter studies of psychological outcomes in living liver donors within the Adult‐to‐Adult Living Donor Liver Transplantation Cohort Study2 (A2ALL‐2) consortium. In total, 271 (91%) of 297 eligible donors were interviewed at least once before donation and at 3, 6, 12, and 24 mo after donation using validated measures. We found that living liver donors reported low rates of major depressive (0–3%), alcohol abuse (2–5%), and anxiety syndromes (2–3%) at any given assessment in their first 2 years after donation. Between 4.7% and 9.6% of donors reported impaired mental well‐being at various time points. We identified significant predictors for donors' perceptions of being better people and experiencing psychological growth following donation, including age, sex, relationship to recipient, ambivalence and motivation regarding donation, and feeling that donation would make life more worthwhile. Our results highlight the need for close psychosocial monitoring for those donors whose recipients died (n=27); some of those donors experienced guilt and concerns about responsibility. Careful screening and targeted, data‐driven follow‐up hold promise for optimizing psychological outcomes following this procedure for potentially vulnerable donors. Abstract : A prospective study of living liver donors across nine transplant centers shows low rates of major depressive, alcohol abuse, and anxiety syndromes, though some donors (such as those whose recipients die) may benefit from close psychosocial monitoring.